ADDRESSING HEALTH PHYSICAL EDUCATION IN SCHOOLS (Fiep Bulletin - online, 2013)
Knowing the level of physical performance of adolescents is critical for planning physical education classes, enabling the development of more effective practices that lead adolescents to develop physical fitness. The present study aims to evaluate aspects of health-related physical fitness of high school students, diagnosing delays in physical performance. The sample consisted of 58.5% of students in the 1st year of high school at a public school in the municipality of Jacareí, ie, 76 adolescents of both sexes with an average age of 15.16 years, 46 males and 30 females. All subjects had their fitness tests to evaluate the motors driven by Project Sport Brazil (PROESP). The data were discussed through descriptive analysis, measures of central tendency (mean) and dispersion (standard deviation) and compared between genders T test, with significance level p
Keywords: Physical Fitness; High School; physical performance.